Violence Against Women in Turkey and the Role of Women Physicians - Büken, Nüket Örnek (Nursing ethics, 2006)
Violence against women is a serious problem in Turkey. The Women and Ethics Commission of the Turkish Physicians’ Association (Ankara Physicians’ Chamber) has undertaken significant work to counteract this. This article gives some indications of the sources of violence and discusses its social and health care implications. The Commission is pivotal in the education of women physicians and in heightening awareness of the situation. An outline is given of this work and recommendations are made on how violence against women can be tackled and eliminated.